The Role of Working Time Flexibility and Work–Life Balance in Enhancing Organizational Commitment: Integration of Social Exchange Theory and Islamic Work Ethics - Maliki Asian, Muhammad; Manurung, Lambok; Ras Muis, Muhammad; Mauliza, Putri (Li Falah: Journal of Islamic Economics and Business, 2026)
This study aims to examine the effect of working time flexibility and work–life balance on organizational commitment within the context of a high-risk operational organization. In the modern work era, both work flexibility and work–life balance have become critical factors in enhancing employee engagement and organizational attachment. This research adopts a quantitative approach using a correlational survey design. The study population consists of 120 employees in an operational service company, with a sample of 92 respondents selected through a simple random sampling technique. Data were analyzed using multiple linear regression, t-test, and F-test with the assistance of SPSS software. The results indicate that both working time flexibility and work–life balance have a significant effect on organizational commitment, both partially and simultaneously. These findings confirm that organizational support in the form of work flexibility and work–life balance plays an essential role in strengthening employee commitment.